Development of Economics Learning, Problematics, and Student Economics Literacy - Trisnawati, Novi; Wulandari, Ruri Nurul Aeni; Soesatyo, Yoyok; Prakoso, Albrian Fiky (International Review of Management and Marketing, 2017)
The study states that students have a high motivation when they are following economics learning. At the time of learning conditions of the students are ready to participate in learning and learning situation during economics lessons the students feel comfortable with their classroom. It is also supported by the using of no teaching aids and a boring learning media. The solution to these problems: 1) add a reference, 2) create a customized power point related to its development, 3) using case studies in teaching, 4) each lecturer is expected to draw up Learning Materials in line with learning outcome of the department. The study states that the regional economy is the most difficult subject that the can be understood by economic education students. This is because the basic of this subject is Mathematical economy because they often calculate Matrix. Keywords: Economics Learning, Problematics, and Economics Literacy JEL Classifications: A2, A23, A29, A12